35. Acceptability of Proposed Stewardship Interventions to Reduce Preoperative Screening and Treatment of Asymptomatic Bacteriuria. (4th December 2021) - Dukes, Kimberly; Walhof, Julia; Brown, Madisen; Gupta, Kalpana; Strymish, Judith; Suh, Daniel; Alexander, Bruce; Au, Vanessa; Beck, Brice; Richardson, Kelly; O'Brien, William; Chan, Jeffrey; et al.
Abstract: Background: In 2019, the IDSA Clinical Practice guidelines on asymptomatic bacteriuria (ASB) recommended that clinicians no longer screen or treat patients for ASB before non-urological surgeries. However, it remains to be seen whether these guideline recommendations alone will produce changes in practice. Understanding clinical decision-making about preoperative urine screening and treatment can help design effective interventions to facilitate guideline concordance and support antibiotic stewardship. Our project objective was to qualitatively assess barriers and facilitators to reducing preoperative urine testing and treatment. Methods: We conducted semi-structured interviews with 24 participants (surgeons, advance practice providers, pharmacists, infectious disease physicians, epidemiologists) at 4 Veterans Administration hospitals. We solicited feedback on 4 proposed interventions (substitution, lab restrictions, audit and feedback, interactive workshop), and invited suggestions on other interventions. Three researchers separately coded 20% of interview notes to sort responses to each intervention into acceptable, possibly acceptable, and not acceptable. The team then compared coding, resolved differences by consensus, and refined the code dictionary to ensure intercoder agreement; then each member coded one third of remaining notes. Results: Participants expressed concerns about de-implementing routine urine testing and treatment for specific procedures and specialties (e.g., cardiothoracic). Some actively sought to identify and treat ASB. Participants found audit and feedback and substitution of different infection-control practices most acceptable. Participants suggested changes to make interventions more acceptable or feasible (e.g., tailoring to procedure, educational tailoring). Participants also identified new potential interventions (e.g. order set changes, collaborative decision making, education on potential harms, identification of testing costs). Table 1. Acceptability of Proposed Interventions by Percentage of Participants. Percentages Do Not Add up to 100% Because Some Interviewees Did Not Answer Every Question. Conclusion: Interventions to optimize urine screening and treatment for patients undergoing surgeries may require tailoring for surgical specialties, and should address clinical concerns about intervention feasibility. Disclosures: Kalpana Gupta, MD, MPH, Abbott (Shareholder)DBC Pri-Med (Consultant)Glaxo Smith Kline (Consultant)Moderna (Shareholder)Nabriva Therapeutics (Consultant)Pfizer (Other Financial or Material Support, Grant to the institution)Qiagen (Consultant)Rebiotix (Consultant)Spero Therapeutics (Consultant)Utility Therapeutics (Consultant) Daniel Suh, MS MPH, General Electric (Shareholder)Merck (Shareholder)Moderna (Shareholder)Smile Direct Club (Shareholder) Bruce Alexander, PharmD, Bruce Alexander Consulting (Independent Contractor) Marin Schweizer, PhD, 3M (Grant/Research Support)PDI (Grant/Research Support)